Cardioprotective Effect of Empagliflozin and Circulating Ketone Bodies During Acute Myocardial Infarction. (12th April 2023) - Santos-Gallego, Carlos G.; Requena-Ibáñez, Juan Antonio; Picatoste, Belen; Fardman, Brian; Ishikawa, Kiyotake; Mazurek, Renata; Pieper, Michael; Sartori, Samantha; Rodriguez-Capitán, Jorge; Fuster, Valentin; Badimon, Juan J.
Abstract : Background: SGLT2i (sodium-glucose cotransporter-2 inhibitors) improve clinical outcomes in patients with heart failure, but the mechanisms of action are not completely understood. SGLT2i increases circulating levels of ketone bodies, which has been demonstrated to enhance myocardial energetics and induce reverse ventricular remodeling. However, the role of SGLT2i or ketone bodies on myocardial ischemia reperfusion injury remains in the dark. The objective of this study is to investigate the cardioprotective potential of empagliflozin and ketone bodies during acute myocardial infarction (MI). Methods: We used a nondiabetic porcine model of ischemia reperfusion using a percutaneous occlusion of proximal left anterior descending artery for 45 minutes. Animals received 1-week pretreatment with either empagliflozin or placebo prior to MI induction. Additionally, a third group received intravenous infusion of the ketone body BOHB (beta-hydroxybutyrate) during the MI induction. Acute effects of the treatments were assessed 4-hour post-MI by cardiac magnetic resonance and histology (thioflavin for area at risk, triphenyltetrazolium chloride staining for MI size). All animals were euthanized immediately postcardiac magnetic resonance, and heart samples were collected. Results: The area at risk was similar in all groups. Empagliflozin treatment increased BOHB levels. Empagliflozin-treated animals showed significantly higher myocardial salvage, smaller MI size (both by cardiac magnetic resonance and histology), less microvascular obstruction, and improved cardiac function (left ventricle ejection fraction and strain). Furthermore, empagliflozin-treated animals demonstrated reduced biomarkers of cardiomyocyte apoptosis and oxidative stress compared with placebo. The BOHB group showed similar results to the empagliflozin group. Conclusions: One-week pretreatment with empagliflozin ameliorates ischemia reperfusion injury, reduces MI size and microvascular obstruction, increases myocardial salvage, preserves left ventricle systolic function, and lowers apoptosis and oxidative stress. Periprocedural intravenous infusion of BOHB during myocardial ischemia also induces cardioprotection, suggesting a role for BOHB availability as an additional mechanism within the wide spectrum of actions of SGLT2i.